Psychological empowerment, job satisfaction and performance among Filipino service workers - Hechanova, Ma. Regina (Archīum Ateneo, 2006)
The present study surveyed 954 employees and their supervisors to determine the relationship of empowerment with job satisfaction and performance in five different service sectors: hotels, food service, banking, call centers, and airlines. Psychological empowerment was positively correlated with both job satisfaction and performance. Although intrinsic motivation was associated with higher levels of empowerment and job satisfaction, contrary to hypothesis, intrinsic motivation did not moderate the relationship between empowerment and job satisfaction and performance. Men reported greater empowerment than women even when job level and performance were controlled for. Cross‐industry analyses indicated differences in empowerment across different types of service sectors with employees in call centers reporting less empowerment compared to employees in hotel, airlines, food establishments, and banks.